Hemodynamic and cardiopulmonary structural and functional changes post TIPSS: A review - Gupta Ajay Kumar1; Tu Rong Fnag1; Tang Ying Mei1; Tong Yu Yun2 (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2019)
A deep understanding of the cardiopulmonary and hemodynamic changes from acute immediate to chronic long-term in the patients undergoing TIPSS is essential for providing a base for timely intervention to decrease the associated morbidity and mortality in the patients post TIPSS . The hemodynamic status of patients has shown a specifi c pattern of alternations in the different time periods post TIPSS. Most of the hemodynamic parameters which increases immediately after TIPSS i.e. including the CO, MAP, PcWP, RAP seems to normalize within 2 months to 1 year duration, the SVR seems to deteriorate further whereas the PPG is decreased immediately after TIPSS and remains constant. Sudden increase in PPG could be an indication of stent occlusion. The systolic function of heart remains unchanged but the diastolic function deteriorates which is indicated by decreased E/A ratio <1 with other cardiac structural changes i.e. increased Left Atrial diameter, Left Ventricle Hypertrophy and increased PcWP . TIPSS increases the incidence of Pulmonary Hypertension which is associated with a high mortality rate. In this article the pattern of changes in hemodynamic, cardiac functional and morphological status in patient's posts TIPSS are reviewed in depth on the basis of studies done in past 22 years.